Isolation and Characterization of Two Persimmon Xyloglucan Endotransglycosylase/Hydrolase (XTH) Genes That Have Divergent Functions in Cell Wall Modification and Fruit Postharvest Softening - Han, Ye; Ban, Qiuyan; Hou, Yali; Meng, Kun; Suo, Jiangtao; Rao, Jingping (Frontiers in Plant Science, 2016)
Fruit cell wall modification is the primary factor affecting fruit softening. Xyloglucan endotransglycosylase/hydrolase (XTH), a cell wall-modifying enzyme, is involved in fruit softening. In this study, two novel XTH genes (DkXTH6 and DkXTH7) were identified from persimmon fruit. Transcriptional profiles of both of the two genes were analyzed in different tissues of persimmon, and in response to multiple hormonal and environmental treatments (gibberellic acid (GA3), abscisic acid (ABA), propylene, and low temperature). Expression of DkXTH6 was positively up-regulated during ethylene production and by propylene and ABA treatments, and suppressed by GA3 and cold treatment. In contrast, DkXTH7 exhibited its highest transcript levels in GA3-treated fruit and cold-treated fruit, which had higher fruit firmness. We found that DkXTH6 protein was localized in cell wall by its signal peptide, while cytoplasmic DkXTH7 protein contained no signal peptide. When expressed in vitro, the recombinant proteins of both DkXTH6 and DkXTH7 exhibited strict xyloglucan endotransglycosylase (XET) activity but no xyloglucan endohydrolase (XEH) activity. The recombinant protein of DkXTH6 showed a higher affinity with small acceptor molecules than the recombinant DkXTH7. Taken together with their opposing expression patterns and subcellular localizations, these results suggested that DkXTH6 might take part in cell wall restructuring and DkXTH7 was likely to be involved in cell wall assembly, indicating their special roles in persimmon fruit softening.